History of the Libyan-British relations 1953-1969: An analytical study of relations between the two countries from the British documents and records. (Journal of Human Sciences, 2018)
This study deals with the study and analysis of an important stage in the history of Libya, which followed the independence of Libya in December 1951. This study is important in the first place because very little was written about the British-Libyan relationship during the 1950s and 1960s. The importance of this study comes also from an important era in the history of Libya that formed the relations between the two countries during the 18 years of the monarchy regime. In addition, the importance of this research can be seen in the bases whose the Libyan-British relations were built during that period and the international strategies that formed the relations between both countries. To highlight the important of this study, the author will address the strategic interests of Britain in Libya in particular and the Mediterranean region in general, and also Libya's strategic interests which called Libya for strengthening its relations with the UK and maintaining strategic rapprochement with Britain. Since this study examines the Libyan-British relations, the author will address the British-Libyan treaty in 1953, as it was the basis of these relations. And as this treaty has been described as a treaty of friendship and alliance, as well as a treaty of protection, the writer will use both descriptions.